Classification based on skeletal muscle mass and the severity of lung emphysema impacts on clinical outcomes after anatomical resection for lung cancer. (18th April 2022) - Tsubokawa, Norifumi; Mimura, Takeshi; Tadokoro, Kazuki; Yamashita, Yoshinori
Abstract: Objectives: Both sarcopenia and lung emphysema are prognostic factors in lung cancer and can be easily assessed using the psoas muscle index and Goddard score, respectively. We investigated the clinical significance of the classification based on psoas muscle index and Goddard score in non-small cell lung cancer. Methods: A total of 303 consecutive patients who underwent anatomical resection for non-small cell lung cancer were retrospectively analyzed. The psoas muscle at the level of the third lumbar vertebrae and Goddard score were measured on preoperative computed tomography. The psoas muscle was adjusted by height as the psoas muscle index (cm 2 /m 2 ). We divided patients into three groups: low-, middle- and high-risk, using cut-off values of psoas muscle index < 6.36 cm 2 /m 2 for males and 3.92 cm 2 /m 2 for females and Goddard score higher than 7. The predictors of postoperative complications and prognosis were examined. Results: High-, middle- and low-risk were present in 30 (10%), 164 (54%) and 109 (36%) patients, respectively. High risk was significantly associated with male sex, low pulmonary function, more comorbidities and increased postoperative complications. High-risk patients showed poorer overall survival than middle- and low-risk patients ( P  < 0.001). Multivariable analysis revealed that high risk was an independent risk factor for postoperative complications and unfavorable prognostic factors ( P  = 0.011, P  = 0.014, respectively). Conclusions: Classification based on psoas muscle index and Goddard score is significantly associated with short- and long-term outcomes in patients with lung cancer. This method can be easily assessed for patients and may help select patients for nutritional support and rehabilitation before surgery. Abstract : The classification based on psoas muscle index and Goddard score is significantly associated with increasing postoperative complications and poor survival. It may help to provide appropriate perioperative management.